Study on Model Scale Rounded-Shape FPSO’s Mooring Lines - Siow, C.L.; Koto, Jaswar; Khairuddin, N.M. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This paper is proposed to discuss the model scale mooring line selection process and preparation for hydrodynamic model experiment. The model scale mooring line should be proper select for model experiment and the error should be minimized because the error in model scale mooring line will be enlarged by the scale factor and influence the design in full scale model. In this study, tensile test experiment for model scale wire ropes was conducted to collect the material properties data of the wire ropes. The data collected from the tensile test is applied to obtain the stiffness of mooring lines in the model scale. To achieve the target to select the model scale mooring lines, the minimum breaking load of the wire ropes and the elongation curve of the wire ropes are collected from tensile test for each wire rope sample. By applying catenary theory and the data from tensile test, the stiffness curve of the mooring line in model scale was estimated. The Difference between the stiffness curve between model scale and full scale is within acceptable at the required experiment range.